What drives a successful Kaizen implementation? An insight from Malaysian automotive manufacturers - Mohd Ghazali, Maarof; Sorooshian, Shahryar; Suhaila, Abdul Hamid (IEOM Society, 2017)
Automotive industry in Malaysia provides vital contributions to Malaysian economy. To remain competitive in a globalised business environment, business players will have to ensure continuous improvement are being implemented as part of their business strategy. This paper presents some of the findings from a larger study on Kaizen implementation among automotive manufacturers and their suppliers in Malaysia. Fifteen semi-structured interviews were conducted among automotive manufacturers and their suppliers in the Klang Valley and Pekan, Pahang. The data which was recorded during the interview was then trancribed and coded before being divided according to relevant themes. Top management commitment, clear Kaizen objective and target, cross-functional effort, good Kaizen knowledge, effective Kaizen control system, the existence of a champion, supportive organizational culture, employee empowerment and role of relevant government agencies are found to be important in Kaizen implementation. Findings from this study are useful to companies which are going to embark into Kaizen or having difficulties to sustain their Kaizen activities. In addition, it could also be useful to respective government agencies to devise strategies that could help automotives companies to sustain their operations in Malaysia.